Analisis Perawatan Injector Akibat Penyumbatan Bahan Bakar Pada Main Engine Kapal - Faulina Khusniawati; Habibi Palippui (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
The auxiliary engine in its operation requires complete combustion to get an effective engine, one of which is to use the injector mechanism. Incomplete combustion can cause the engine to not work optimally, it will even cause damage to theengine so that it requires the cost of repair and replacement of its spare parts. The injector has a way of working by providing high-pressure fuel from the injection pump. The main function of a diesel injector is a device to shrink fuel until it breaks into smooth parts (mist) in high temperatures. The high temperature will have an impact on the engine so that regular maintenance is needed on the engine injector. This research uses data collection methods conducted by library research and document studies. This research includes: finding data of the main engine (injector), analyzing and identifying damage to the injector, repairing, and testing the injector engine.